2016
DOI: 10.1016/j.difgeo.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

H-contact unit tangent sphere bundles of Riemannian manifolds

Abstract: A contact metric manifold is said to be H-contact, if the characteristic vector field is harmonic. We prove that the unit tangent bundle of a Riemannian manifold M equipped with the standard contact metric structure is H-contact if and only if M is 2-stein.2010 Mathematics Subject Classification. Primary 53C25, 53D10; Secondary 53B20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A contact metric manifold whose characteristic vector field ξ is a harmonic vector field is called an H-contact manifold. Nikolayevsky and Park [13] showed that for a Riemannian manifold M, T 1 M equipped with the standard contact metric structure is H-contact if and only if M is 2-stein. Gilkey, Swann, and Vanhecke [10] showed that a 4-dimensional manifold M is 2-stein if and only if locally there is a choice of orientation of M for which the metric is self-dual and Einstein ([10, Theorem 2.6]).…”
Section: Introductionmentioning
confidence: 99%
“…A contact metric manifold whose characteristic vector field ξ is a harmonic vector field is called an H-contact manifold. Nikolayevsky and Park [13] showed that for a Riemannian manifold M, T 1 M equipped with the standard contact metric structure is H-contact if and only if M is 2-stein. Gilkey, Swann, and Vanhecke [10] showed that a 4-dimensional manifold M is 2-stein if and only if locally there is a choice of orientation of M for which the metric is self-dual and Einstein ([10, Theorem 2.6]).…”
Section: Introductionmentioning
confidence: 99%
“…, where R X : T x M → T x M is the Jacobi operator (for further properties of 2-stein manifolds see [N3,NP]).…”
Section: Introductionmentioning
confidence: 99%